Analisis Perbandingan Metode MAUT dan OCRA dalam Rekomendasi Produk Tabir Surya Terbaik - Harahap, Amran Saleh; Tanjung, Dewi Maulida Sari; Soeb Aripin (Journal of Decision Support System Research, 2024)
This research aims to conduct a comparative analysis between the MAUT (Multi-Attribute Utility Theory) and OCRA (Order of Comparative Risk Assessment) methods in the context of recommending the best sunscreen products. A Decision Support System (DSS) is employed as the underlying tool for selecting the most suitable products based on predefined criteria. The research findings indicate that both methods yield the same best alternative, which is the product "The Originote" with an A8 ranking. The MAUT method produces the best preference value of 0.53, while the OCRA method yields the best preference value of 2.455. These results reveal that in the data testing conducted, the OCRA method takes the first rank with higher preferences compared to the MAUT method. This research offers valuable insights into the selection of the best sunscreen products by utilizing two different methods, which can assist consumers and stakeholders in making more informed and data-driven decisions. These findings can serve as a basis for further developments in decision analysis methods within the context of sunscreen products and similar items.